The history of the development of anabolic-androgenic steroids - Dotson, J. L.; Brown, R. T. (Pediatric Clinics of North America, 2007)
The history of anabolic-androgenic steroids (AASs) is an interesting tale that has its roots in ancient "endocrinology." More than 6000 years ago, farmers noted enhanced domestication of animals after castration. The development of AASs, and, later, their artificial synthesis, have remained a hot topic in scientific research and pharmaceuticals. Over the years, AASs have been used as a proposed treatment for a wide variety of ailments, despite deleterious side effects. Unfortunately, they have been, and still are, abused by body builders, athletes, and teens.